“DEPHENCE” system—a novel regimen of therapy that is urgently needed in the high-grade serous ovarian cancer—a focus on anti-cancer stem cell and anti-tumor microenvironment targeted therapies - Wilczyński, Jacek R.; Wilczyński, Miłosz; Paradowska, Edyta (Frontiers in Oncology, 2023)
Ovarian cancer, especially high-grade serous type, is the most lethal gynecological malignancy. Lack of screening programs and scarce symptomatology result in the late diagnosis in about 75% of affected women. Despite very demanding and aggressive surgical treatment, multiple-line chemotherapy regimens and both approved and clinically tested targeted therapies the overall survival of patients is still unsatisfactory and disappointing. Research studies have recently brought some more understanding of the molecular diversity of the ovarian cancer, its unique intraperitoneal biology, the role of cancer stem cells and the complexity of tumor microenvironment. There is a growing evidence, that individualization of the treatment adjusted to the molecular and biochemical signature of the tumor, as well as, to the medical status of the patient should replace or supplement the foregoing therapy. In this review, we have proposed the principles of the novel regimen of the therapy called by us „DEPHENCE” system, and we have extensively discussed the results of the studies focused on the ovarian cancer stem cells, other components of cancer metastatic niche and finally, clinical trials targeting these two environments. Through this we have tried to present the evolving landscape of treatment options, and put flesh on the experimental approach to attack the high-grade serous ovarian cancer multidirectionally, correspondingly to the „DEPHENCE” system postulates.